2021
DOI: 10.3390/v13091867
|View full text |Cite
|
Sign up to set email alerts
|

Direct Metatranscriptomic Survey of the Sunflower Microbiome and Virome

Abstract: Sunflowers (Helianthus annuus L.) are susceptible to multiple diseases in field production. In this study, we collected diseased sunflower leaves in fields located in South Dakota, USA, for virome investigation. The leaves showed visible symptoms on the foliage, indicating phomopsis and rust infections. To identify the viruses potentially associated with the disease diagnosed, symptomatic leaves were obtained from diseased plants. Total RNA was extracted corresponding to each disease diagnosed to generate libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Before the advent of metagenomics, the ICTV criterion of 50% amino acid identity was sufficient, because the limited number of known species was sufficiently distinct (e.g., only 30% identity between Saccharomyces cerevisiae virus L-A and Saccharomyces cerevisiae virus L-BC in the 717-amino-acid (aa) region of highest similarity) ( 49 ). However, the numerous Totivirus species identified here and in other metagenomics studies ( 36 , 50 ) presented less clear tendencies that could eventually suggest reconsideration of demarcation criteria for the genus (e.g., harmonizing rules with victoriviruses that also belong to the Totiviridae family and present a demarcation threshold of 60% aa identity).…”
Section: Discussionmentioning
confidence: 58%
“…Before the advent of metagenomics, the ICTV criterion of 50% amino acid identity was sufficient, because the limited number of known species was sufficiently distinct (e.g., only 30% identity between Saccharomyces cerevisiae virus L-A and Saccharomyces cerevisiae virus L-BC in the 717-amino-acid (aa) region of highest similarity) ( 49 ). However, the numerous Totivirus species identified here and in other metagenomics studies ( 36 , 50 ) presented less clear tendencies that could eventually suggest reconsideration of demarcation criteria for the genus (e.g., harmonizing rules with victoriviruses that also belong to the Totiviridae family and present a demarcation threshold of 60% aa identity).…”
Section: Discussionmentioning
confidence: 58%
“…Wang et al confirmed that Huangkui capsules can inhibit glomerular immunity of the organism to abate the inflammatory response, and it also inhibits platelet aggregation to mitigate the impairment of kidney function. In addition, the Huangkui capsule also has the effect of scavenging oxygen free radicals, reducing urine protein, blood urea nitrogen, and muscle libido [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the numerous Totivirus species identified here and in other metagenomics studies (34,48) presented less clear tendencies that could eventually suggest to reconsider demarcation criteria for the genus (e.g. harmonizing rules with victoriviruses that also belong to the Totiviridae family and present a demarcation threshold of 60% aa identity).…”
Section: Network and Clustering Analyses Also Highlighted Different V...mentioning
confidence: 67%